A Comparative Study on the Thermodynamics of Halogen Bonding of Group 10 Pincer Fluoride Complexes. Issue 16 (28th February 2020) - Joksch, Markus; Agarwala, Hemlata; Ferro, Monica; Michalik, Dirk; Spannenberg, Anke; Beweries, Torsten
Abstract: The thermodynamics of halogen bonding of a series of isostructural Group 10 metal pincer fluoride complexes of the type [(3, 5‐R2 ‐ t Bu POCOP t Bu )MF] (3, 5‐R2 ‐ t Bu POCOP t Bu = κ 3 ‐C6 HR2 ‐2, 6‐(OP t Bu2 )2 with R=H, t Bu, COOMe; M=Ni, Pd, Pt) and iodopentafluorobenzene was investigated. Based on NMR experiments at different temperatures, all complexes 1‐ t Bu (R= t Bu, M=Ni), 2‐H (R=H, M=Pd), 2‐ t Bu (R= t Bu, M=Pd), 2‐COOMe (R=COOMe, M=Pd) and 3‐ t Bu (R= t Bu, M=Pt) form strong halogen bonds with Pd complexes showing significantly stronger binding to iodopentafluorobenzene. Structural and computational analysis of a model adduct of complex 2‐ t Bu with 1, 4‐diiodotetrafluorobenzene as well as of structures of iodopentafluorobenzene in toluene solution shows that formation of a type I contact occurs. Abstract : Pincer complexes studied : Group 10 POCOP ( κ 3 ‐C6 HR2 ‐2, 6‐(OP t Bu2 )2 ; R=H, t Bu) fluoride complexes show pronounced halogen bonding with iodopentafluorobenzene in toluene. Along an isostructural series of complexes, Pd fluorides show the strongest interactions.